From Rain Man to Sherlock: Theological Reflections on Metaphor and ASD. Issue 2 (June 2015) - Howell, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> The discipline of practical theology has created a significant body of work considering the theological implications of disability and illness. Within that, less attention has been given to High Functioning Autistic Spectrum Disorder (HFASD), also described as Asperger Syndrome. It may be that this is because more attention has been focused on the associated and more easily diagnosable condition of autism. Disability theology has also recognized the existence and function of metaphor, both within the Bible and society. Emphasis on liberation has been a particular theme, with lesser attention given to hermeneutical approaches. This paper attempts to bring together the experience of HFASD together with the historical study of metaphor and, in so doing, suggests possible avenues for further research. The canonical-linguistic hermeneutic of Vanhoozer serves as a foundation for theological reflection.